Mex67p, a novel factor for nuclear mRNA export, binds to both poly(A)+ RNA and nuclear pores - Segref, Alexandra; Sharma, Kishore; Doye, Valérie; Hellwig, Andrea; Huber, Jochen; Lührmann, Reinhard; Hurt, Ed (The EMBO journal, 1997)
An essential cellular factor for nuclear mRNA export called Mex67p which has homologous proteins in human and Caenorhabditis elegans was identified through its genetic interaction with nucleoporin Nup85p. In the thermosensitive mex67‐5 mutant, poly(A)+ RNA accumulates in intranuclear foci shortly after shift to the restrictive temperature, but NLS‐mediated nuclear protein import is not inhibited. In vivo, Mex67p tagged with green fluorescent protein (GFP) is found at the nuclear pores, but mutant mex67‐5-GFP accumulates in the cytoplasm. Upon purification of poly(A)+ RNA derived from of UV‐irradiated yeast cells, Mex67p, but not nucleoporins Nup85p and Nup57p, was crosslinked to mRNA. In a two‐hybrid screen, a putative RNA‐binding protein with RNP consensus motifs was found to interact with the Mex67p carboxy‐terminal domain. Thus, Mex67p is likely to participate directly in the export of mRNA from the nucleus to the cytoplasm.